Предмет: Алгебра,
автор: макс969
Помогите Пожалуйста НУжна очень помочь
Приложения:
Ответы
Автор ответа:
0
а) (а-2)(а+2)(а²+4)= 25а²-16
(а²-4)(а²+4)=25а²-16
а∧4-16=25а²-16
а∧4-25а²=0
а²(а²-25)=0
а²=0
а=0
а²-25=0
а²=25
а= +- 5
б) (х-1)(х+1)(х²+1)=6х²-1
(х²-1)(х²+1)=6х²-1
х∧4-1=6х²-1
х∧4-6х²=0
х² (х²-6)=0
х²=0
х=0
х²-6=0
х²=6
х= + - √6
(а²-4)(а²+4)=25а²-16
а∧4-16=25а²-16
а∧4-25а²=0
а²(а²-25)=0
а²=0
а=0
а²-25=0
а²=25
а= +- 5
б) (х-1)(х+1)(х²+1)=6х²-1
(х²-1)(х²+1)=6х²-1
х∧4-1=6х²-1
х∧4-6х²=0
х² (х²-6)=0
х²=0
х=0
х²-6=0
х²=6
х= + - √6
Похожие вопросы
Предмет: Математика,
автор: aygun2008arzu1989
Предмет: Алгебра,
автор: yudinslava028
Предмет: Физика,
автор: anvarovamarjona267
Предмет: Математика,
автор: Кравченко79
Предмет: Математика,
автор: arevichka14